Assessment of changes in soil contact stress depending on tractor tire parameters - Savelii Kukharets; Andrii Zabrodskyi; Bohdan Sheludchenko; Algirdas Jasinskas; Rolandas Domeika; Egidijus Šarauskis (Scientific Reports)
Abstract Soil compaction by agricultural machinery in general by and tractors in particular is an important problem in modern agricultural production. Such compaction destroys the soil structure, creates unfavorable physical parameters of the soil, and as a result, reduces crop yields. Therefore, it is important to clearly establish how the tractor wheels affect the soil. The experiments were conducted on the sandy loam soil by using CLAAS Xerion 5000 tractor with TRELLEBORG IF 900/60 R42 tires with internal pressures varying from 0.08 to 0.24 MPa in 0.04 MPa increments. To determine the stress propagation a developed simulation model was adapted to the parameters of the tractor in use. The iterative method was used for the numerical determination of the soil stress state. The impact of soil compaction starting from a 40 cm depth is not noticeable following the tractor’s pass. In fact, from a depth of 40 cm, the normal stresses reach equilibration according to the developed mathematical model. From a depth of 20 cm, the soil compaction pattern is similar for all tire widths tested. Tires with a width up to 10 cm, 0.92 m wide tires compact the soil 25.4% less on average than tires with a width up 0.872 m wide tires. To the depth of 20 cm, tires with a width up the 0.92 m wide tires compact the soil 18.9% less on average than the tires with a width up 0.872 m, and to a depth of 30 cm – only 5.1% less. The tractor with a working tire width of 0.92 m and an axle load of 119.5 kN generate contact stresses on the field surface of up to 150 kPa, which is a permissible load for soil structure safety. Thus, the suggested simulation model of the soil stress state is suitable for use, and studies and modeling advance the idea that using wider tires results in a more equitable distribution of loads. The proposed model for analyzing stress propagation in soil enables to estimate the potential adverse impacts of wheeled or tracked agricultural machinery on soil structure by assessing stress levels that may disrupt or damage soil integrity, with the stresses varying according to the specific physical and chemical properties of each soil type.